68Ga-NODAGA-RGDyK for αvβ3 integrin PET imaging - Buchegger, F.; Viertl, D.; Baechler, S.; Dunet, V.; Kosinski, M.; Poitry-Yamate, C.; Rüegg, C.; Prior, J. O. (Nuklearmedizin - NuclearMedicine, 2011)
Aim: To visualize neovasculature and/or tumour integrin αvβ3 we selected the binding moiety Arg-Gly-Asp-D-Tyr-Lys (RGDyK) coupled to NODAGA for labeling with 68Ga. Methods: NODAGA-RGDyK (ABX) was labeled with the 68Ga eluate from the 68Ge generator IGG100 using the processor unit PharmTracer. Biodistribution was measured in female Hsd mice sacrificed 10, 30, 60 and 90 min after i. v. injection of 68Ga-NODAGA-RGDyK for OLINDA dosimetry extrapolated to humans. Tumour targeting was studied in SCID mice bearing A431 and other tumour transplants using microPET and biodistribution measurements. Results: Effective half-life of 68Ga-NODAGA-RGDyK was ∼25 min for total body and most organs except liver and spleen that showed stable activity retention. With a bladder voiding interval of 0.5 h the calculated effective dose (ED) was 0.012 and 0.016 mSv/MBq for males and females, respectively. Rapid uptake within 10 min was observed in A431 tumours with dynamic PET followed by a slow release. Biodistribution measurements showed a 68Ga-NODAGARGDyK uptake in A431 tumours of 3.4 ± 0.4 and 2.7 ±0.3%ID/g at 1 and 2 h, respectively. Similar uptakes were observed in a mouse and human breast and ovarian cancer xenografts. Co-injection of excess (5 mg/kg) unlabeled NODAGA- RGDyK with the radiotracer reduced tumour uptake at one hour to 0.23 ± 0.01%ID/g, but similarly decreased uptake in normal organs as well. When unlabeled peptide was injected 15 min after 68Ga- NODAGA- RGDyK, uptake diminished particularly in tumour and adrenals, suggestive of a different binding mode compared with other normal tissues. Conclusion: NODAGA- RGDyK was reliably labeled with 68Ga and revealed a predicted ED of 0.014 mSv/MBq. Tumour uptake was rapid and significant and was chased with unlabeled RGDyK in a similar manner as adrenal uptake.
Keywords: Integrin; αvβ3; RGD-peptide; cyclic RGDyK; 68Ga-NODAGA-RGDyK; PET imaging